Social Entrepreneurship Model For Village Tourism Business With A Triple Helix Collaborative Approach - Sudarmiatin; Raisa Fitri; Iva Khoirul Mala (Indonesian Journal of Business Analytics, 2025)
The objectives of this study are: (1) to describe the problems faced by Sumberpasir Village in community empowerment; (2) to develop a social entrepreneurship model through a triple helix approach; and (3) to identify supporting and inhibiting factors. This research is basic research focused on developing a social entrepreneurship model through a collaborative triple helix approach. The research location is Sumberpasir Tourism Village, Pakis District, Malang Regency. The subjects of this study were all stakeholders in Sumberpasir Tourism Village. The results show that (1) the main problem is limited human resource capabilities; (2) a social entrepreneurship model through a triple helix approach is recommended; and (3) the opportunities to improve the performance of Sumberpasir Tourism Village through digital media.